Writing Habits of the Undergraduate Level EFL Learners: A Survey - Pathan, Md. Arif Khan (International Journal of Language and Literary Studies, 2025)
From personal to professional, intellectual to recreational; writing benefits a student in every sphere of life. The significance of writing in learning a new language is also undeniable. In Bangladeshi schools and colleges, reading and writing-based English learning system provides students with a lot of opportunities to practice writing and improve their writing skills. Unfortunately, the majority of the undergraduate level students are found very incompetent in writing English. It is assumed that students are used to writing only academic subjects. They prefer to memorize notes and write only for academic purposes, more particularly for exam purposes. The current study attempts to justify the assumption through a five-point Likert-scale survey. A questionnaire consisting of ten questions is used to investigate what the students write or like to write in English other than their academic subjects regularly. The study discovers that the majority of the students do not regularly write non-academic English texts like stories, poems, letters, memorable events, news reports, etc. They write them occasionally. Besides, there are a significant number of students who either rarely or never write this type of writing. This shows that the students are either not truly interested in extra-curricular writing activities or not aware of the benefits of extensive writing. Although there are a lot of things that they can write regularly to develop their writing skills, they don’t do that and consequently can’t develop good writing habits in their daily lives.